Solanum tuberosum L. Sp. Pl. - OVCHINNIKOVA, ANNA; KRYLOVA, EKATERINA; GAVRILENKO, TATJANA; SMEKALOVA, TAMARA; ZHUK, MIKHAIL; KNAPP, SANDRA; SPOONER, DAVID M. (Zenodo, 2011)
4. Solanum tuberosum L. Sp. Pl. 185. 1753 . Battata tuberosa Hill, Hort. Kew. 148. 1768, Lycopersicon tuberosum (L.) Mill., Gard. Dict. ed. 8, no. 7. 1768, Solanum esculentum Neck., Delic. Gallo-Belg. 1: 119. 1768, Solanum tuberosum L. var. vulgare Hook. f., Bot. Antarct. Voy. I. (Fl. Antarct.) 2: 329. 1846, Solanum tuberosum L. var. cultum A.DC. Arch. Sci. Phys. Nat. ser. 3, 15: 437. 1886, Solanum tuberosum L. var.? vulgare Macloskie, Rep. Princeton Univ. Exped. Patagonia 8: 707. 1905, Solanum cultum (A.DC.) Berthault, Recherc. Bot. var. Cult. Solanum tuberosum , etc. 127, 128. 1911. Type: cultivated in Uppsala, Anon. (lectotype, LINN! [LINN 248.12, BH neg. 6799], designated by Hawkes, 1956b: 106). [C] Figure 4. Solanum sinense Blanco, Fl. Filip. ed. 1: 137. 1837. Type: Philippines. Sin. loc. cultivated, F. Blanco s.n. (no specimens found). [C]. Solanum tuberosum L. var. leonhardianum Alef., Landw. Fl. 137. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. melanoceras Alef., Landw. Fl. 137. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 29, designated here). [C]. Solanum tuberosum L. var. californicum Alef., Landw. Fl. 138. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. erythroceras Alef., Landw. Fl. 138. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. holsaticum Alef., Landw. Fl. 138. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. cucumerinum Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. julianum Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. menapianum Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. platyceras Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. reniforme Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. tener Alef., Landw. Fl. 139. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). Solanum tuberosum L. var. brachyceras Alef., Landw. Fl. 140. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. helenanum Alef., Landw. Fl. 140. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. laurentianum Alef., Landw. Fl. 140. 1866. Type: no specimens found (lectotype, Putsch, 1819, Monographie der Kartoffel, f. 2, designated here). [C]. Solanum tuberosum L. var. putscheanum Alef., Landw. Fl. 140. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. sesquimensale Alef., Landw. Fl. 140. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. xanthoceras Alef., Landw. Fl. 140. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. bertuchii Alef., Landw. Fl. 141. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. saccharatum Alef., Landw. Fl. 141. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 19, designated here). [C]. Solanum tuberosum L. var. schnittspahnii Alef., Landw. Fl. 141. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. strobilinum Alef., Landw. Fl. 141. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. borsdorfianum Alef., Landw. Fl. 142. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. cordiforme Alef., Landw. Fl. 142. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 3, designated here). [C]. Solanum tuberosum L. var. nobile Alef., Landw. Fl. 142. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 10, designated here). [C]. Solanum tuberosum L. var. album Alef., Landw. Fl. 143. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. batatinum Alef., Landw. Fl. 143. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. nucinum Alef., Landw. Fl. 143. 1866. Type: no specimens found (lectotype, Putsch, 1819, Monographie der Kartoffel, f. 21, designated here). [C]. Solanum tuberosum L. var. peruvianum Alef., Landw. Fl. 143. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 23, designated here). [C]. Solanum tuberosum L. var. alaudinum Alef., Landw. Fl. 144. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. anglicum Alef., Landw. Fl. 144. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. bufoninum Alef., Landw. Fl. 144. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. hispanicum Alef., Landw. Fl. 144. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. pecorum Alef., Landw. Fl. 144. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 31, designated here). [C]. Solanum tuberosum L. var. rugiorum Alef., Landw. Fl. 144. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 30, designated here). [C]. Solanum tuberosum L. var. conocarpum Alef., Landw. Fl. 145. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. praecox Alef., Landw. Fl. 145. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 6, designated here). [C]. Solanum tuberosum L. var. praedicandum Alef., Landw. Fl. 145. 1866. Type: no specimens found (lectotype, Putsch, 1819, Monographie der Kartoffel, f. 26, designated here). Solanum tuberosum L. var. rockii Alef., Landw. Fl. 145. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 9, designated here). [C]. Solanum tuberosum L. var. drakeanum Alef., Landw. Fl. 146. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. elongatum Alef., Landw. Fl. 146. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. tinctorium Alef., Landw. Fl. 146. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. vuchefeldicum Alef. , Landw. Fl. 146. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 27, designated here). [C]. Solanum tuberosum L. var. aethiopicum Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. hassicum Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. kaunitzii Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. merceri Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. norfolcicum Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. rossicum Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. ulmense Alef., Landw. Fl. 147. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. cepinum Alef., Landw. Fl. 148. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. fragariinum Alef., Landw. Fl. 148. 1866. Solanum tuberosum L. convar. fragariinum (Alef.) Danert, Kulturpβanze 4: 126. 1956. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. palatinatum Alef., Landw. Fl. 148. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 5, designated here). [C]. Solanum tuberosum L. var. versicolor Alef., Landw. Fl. 148. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 7, designated here). [C]. Solanum tuberosum L. var. corsicanum Alef., Landw. Fl. 149. 1866. Type: cultivated in Darmstadt, Germany (no specimens found). [C]. Solanum tuberosum L. var. salamandrinum Alef., Landw. Fl. 149. 1866. Type: cultivated in Darmstadt, Germany (no specimens found, lectotype, Putsch, 1819, Monographie der Kartoffel, f. 8, designated here). [C]. Solanum tuberosum L. var. chiloense A.DC., Arch. Sci. Phys. Nat. ser. 3, 15: 437. 1886. Solanum chiloense (A.DC.) Berthault, Ann. Sci. Agron. Franç. Étrangère, ser. 3, 6: 180. 1911. Type: Chile. Region X (Los Lagos): Isla Chiloé, 1862, R. A. Philippi s.n. (holotype, G! [G 00070236]). [C]. Solanum maglia Schltdl. var. guaytecarum Bitter, Repert. Spec. Nov Regni Veg. 12: 2. 1913. Solanum tuberosum L. var. guaytecarum (Bitter) Hawkes, Proc. Linn. Soc. Lond. 166: 130. 1956. Type: Chile. Region X (Los Lagos): Prov. Chiloé, Guaytecas Archipelago, 6.iii.1857, N. Funck 102 C (holotype, P! [P 00384639]). [C]. Solanum tenuifilamentum Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 603. 1929. Type: cultivated in Leningrad from tuber accession collected in Peru (Cusco: Chinchero, S. Juzepczuk 1355 ), viii.1929, S. Juzepczuk [1255] (lectotype, LE!, designated by Ovchinnikova et al ., 2009: 586). [A]. Solanum phureja Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 604. 1929. Type: cultivated in Leningrad from tuber accession 4855/3587 collected in Bolivia (La Paz: Sorata, S. Juzepczuk 1654 ), 1929, S. Juzepczuk [1654] (lectotype, WIR! [WIR-36885], designated by Korovina, Belozor & Chernomorskaja, 1985: 19; isolectotype, K! [K 000658022]). [A]. Solanum goniocalyx Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 605. 1929. Solanum stenotomum Juz. & Bukasov subsp. goniocalyx (Juz. & Bukasov) Hawkes, Rep. (Annual) Scott. Pl. Breed. Sta. 1963: 157. 1963. Type: cultivated in Leningrad from tuber accession collected in Peru (Cerro de Pasco, S. Juzepzcuk 571 ), 1929, S. Juzepczuk [571] (lectotype, LE!, designated by Gorbatenko & Hawkes, 1996: 552; isolectotype, LE!). [A]. Solanum rybinii Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 606. 1929. Type: cultivated in Leningrad from tuber accession collected in Colombia (Cundinamarca: near Bogotá, S. Bukasov 46 ), ix.1929, S. Juzepczuk s.n. (lectotype, LE!, designated here). [A]. Solanum stenotomum Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 609. 1929. Type: cultivated in Leningrad from tuber accession 4870/3537 collected in Bolivia (La Paz, S. Juzepczuk 1681 ), 1929, S. Juzepczuk [1681] 1552 (lectotype, WIR! [WIR-18777], designated here). [A]. Solanum andigenum Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 609. 1929, Solanum tuberosum L. subsp. andigenum (Juz. & Bukasov) Hawkes, Proc. Linn. Soc. Lond. 166: 130. 1956. Type: cultivated in Leningrad from tuber accession collected in Peru (Pasco: Cerro de Pasco, 1927, S. Juzepczuk 598 ), ix.1929, S. Juzepczuk [598] (lectotype, LE! [unnumbered photograph mounted on K 000658023!], designated here; isolectotypes, K! [K 000065896, K 000658097, K 000658098, K 000658099]). [A]. Figure 5. Solanum boyacense Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 609. 1929. Solanum rybinii Juz. & Bukasov var. boyacense (Juz. & Bukasov) Hawkes, Potato Collect. Exped. Mexico & S. Amer. 2 Syst. Classific. Collect. 2, 70. 1944. Type: cultivated in Leningrad from tuber accession collected in Colombia (Boyacá: Chochonta, near Tunja, S. Bukasov 20 ), ix.1929, S. Juzepczuk s.n. (lectotype, LE!, designated here). [A]. Solanum chaucha Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 609. 1929. Type: cultivated in Leningrad from tuber accession collected in Peru (Cusco: near Cusco, San Jeronimo, S. Juzepczuk 1010 ), viii.1929, S. Juzepczuk [1010] (lectotype, LE!, designated by Ovchinnikova et al ., 2009: 583; isolectotypes, K! [K 000658008, K 000658177], LE! [2 additional sheets]). [A]. Solanum mamilliferum Juz. & Bukasov, Trudy Vsesoyuzn. S ”ezda Gen. Selekts. Semenov. Plemen. Zhivotnov. 3: 609. 1929. Type: cultivated in Leningrad from tuber accession 4899/3415 collected in Peru (Cusco: Ppisac, S. Juzepczuk 1001 ), 1928, S. Juzepczuk 1498 (lectotype, WIR! [WIR-18611], designated by Ovchinnikova et al ., 2009: 584; isolectotype, K! [K 000658176]). [A]. Solanum andigenum Juz. & Bukasov var. mexicanum Bukasov, Trudy Prikl. Bot. Suppl. 47: 202, 516. 1930, Solanum andigenum Juz. & Bukasov forma tolucanum Bukasov, Trudy Prikl. Bot. Suppl. 47: 202, 516. 1930. Type: cultivated in Leningrad from tuber accession 4001/1 collected in Mexico (Mexico: Cuautzingo, Anon. [S. Bukasov] 1 ), 1929, S. Juzepczuk s.n. (lectotype, WIR! [WIR-38364], designated here). [A]. Solanum andigenum Juz. & Bukasov forma chalcoense Bukasov, Trudy Prikl. Bot. Suppl. 47: 204, 517. 1930. Type: cultivated in Leningrad from tuber accession collected in Mexico (Toluca: Cuatzingo (near Chalco), S. Bukasov 3 & 4 DF: Cocayan and Ajusco, M. C. Antipovich s.n. ) (no specimens found). [A]. Solanum andigenum Juz. & Bukasov forma guatemalense Bukasov, Trudy Prikl. Bot. Suppl. 47: 205, 518. 1930. Type: cultivated in Leningrad from tuber accession 4018 collected in Guatemala (Escuintla, Anon. [S. Bukasov] 13 ), 1929, S. Bukasov [13] (lectotype, WIR! [WIR-38370], designated here). [A]. Solanum andigenum Juz. & Bukasov var. colombianum Bukasov, Trudy Prikl. Bot. Suppl. 47: 205. 1930, Solanum andigenum Juz. & Bukasov forma tocanum Bukasov, Trudy Prikl. Bot. Suppl. 47: 205. 1930. Type: cultivated in Leningrad from tuber accession collected in Colombia (Cundinamarca, S. Juzepczuk 44 ), 1930, S. Juzepczuk [44] (lectotype, WIR! [WIR-38416], designated here). [A]. Solanum andigenum Juz. & Bukasov var. cuzcoense Bukasov & Lechn., Trudy Prikl. Bot. Suppl. 47: 205. 1930. Solanum andigenum Juz. & Bukasov convar. longiacuminatum Lechn., Trudy Prikl. Bot. 79: 47. 1983. Type: cultivated in Leningrad from tuber accession 4355/3291 collected in Peru (Cusco: Paucartambo, S. Juzepczuk 1348 ), no date, V. S. Lekhnovich s.n. (lectotype, WIR! [WIR-37225], designated here). [A]. Solanum andigenum Juz. & Bukasov forma caiceda Bukasov, Trudy Prikl. Bot. Suppl. 47: 208. 1930. Type: cultivated in Leningrad from tuber accession 4039 collected in Colombia (Cundinamarca: Chipaque, Anon. [S. Bukasov] 49b ), 1931, S. Juzepczuk [49b] (lectotype, WIR! [WIR-38498], designated here). [A]. Solanum andigenum Juz. & Bukasov forma lisarassa Bukasov, Trudy Prikl. Bot. Suppl. 47: 209, 520. 1930. Type: cultivated in Leningrad from tuber accession 4083 collected in Colombia (Cundinamarca: near Bogotá, Chipaque, S. Juzepczuk 35 ), 1929, S. Juzepczuk [35] 1449 (lectotype, WIR! [WIR-18661], designated here). [A]. Solanum andigenum Juz. & Bukasov forma rosada Bukasov, Trudy Prikl. Bot. Suppl. 47: 210, 250, fig. 103. 1930. Type: cultivated in Leningrad from tuber accession 4169 collected in Colombia (Pasto: Popayán, Anon. [S. Bukasov] 98a ), 1929, S. Juzepczuk [98a] (lectotype, WIR! [WIR-38372], designated here). [A]. Solanum andigenum Juz. & Bukasov var. hederiforme Bukasov, Trudy Prikl. Bot. Suppl. 47: 521. 1930. Type: cultivated in Leningrad from tuber accession collected in Colombia (Caldas: Manizales, Anon. [S. Bukasov] 84 ), 1928, S. Bukasov [84] (lectotype, WIR! [WIR-38381], designated here). [A]. Solanum stenotomum Juz. & Bukasov var. ccami Bukasov, Trudy Prikl. Bot. Suppl. 58: 33, 164. 1933. Solanum stenotomum Juz. & Bukasov forma ccami (Juz. & Bukasov) Hawkes, Potato Collect. Exped. Mexico & S. Amer., 2, Syst. Classific. Collect. 55. 1944. Type: cultivated in Leningrad from tuber accession 4678/3605 collected in Bolivia (La Paz: Titicaca, Tiahuanaco, S. Juzepczuk 1645 ), 1929, S. Juzepczuk [1645] (lectotype, WIR!, designated here). [A]. Solanum stenotomum Juz. & Bukasov var. ppitiquina Bukasov, Trudy Prikl. Bot. Suppl. 58: 33. 1933. Type: cultivated in Leningrad from tuber accession 4862/3446 collected in Peru (Cusco, S. Juzepczuk 1319 ), 1929, S. Juzepczuk [1319] (lectotype, WIR!, designated here). [A]. Solanum andigenum Juz. & Bukasov forma lilacinoflorum Bukasov, Trudy Prikl. Bot. Suppl. 58: 38. : Published as part of OVCHINNIKOVA, ANNA, KRYLOVA, EKATERINA, GAVRILENKO, TATJANA, SMEKALOVA, TAMARA, ZHUK, MIKHAIL, KNAPP, SANDRA & SPOONER, DAVID M., 2011, Taxonomy of cultivated potatoes (Solanum section Petota: Solanaceae), pp. 107-155 in Botanical Journal of the Linnean Society 165 (2) on pages 121-139, DOI: 10.1111/j.1095-8339.2010.01107.x, http://zenodo.org/record/6326420 : {"references": ["Hawkes JG. 1956 b. Taxonomic studies on the tuber-bearing Solanum s. I. Solanum tuberosum and the tetraploid species complex. Proceedings of the Linnean Society of London 166: 97 - 144.", "Putsch CWE. 1819. Versuch einer Monographie der Kartoffeln; oder ausfuhrliche Beschreibung der Kartoffeln nach ihrer Geschichte, Charakteristik, Kultur und Anwendung in Deutschland. Weimar: Lands-Industrie Comptoire.", "Ovchinnikova AB, Krylova EA, Dorofeyev VI, Smekalova TN, Chukhina IG, Gavrilenko TA. 2009. Type specimens of cultivated species of Solanum section Petota kept in the herbaria of St. Petersburg (WIR, LE). Botanicheskii Zhurnal (Moscow & Leningrad) 94: 581 - 587 (in Russian with English summary).", "Korovina ON, Belozor NI, Chernomorskaja NM. 1985. The catalogue of types of the plants kept in VIR herbarium (WIR), part 2. Leningrad: Vavilov Institute (in Russian).", "Gorbatenko L, Hawkes JG. 1996. The designation of a lectotype for a cultivated potato species, Solanum goniocalyx Juz. & Bukasov. Kew Bulletin 51: 552.", "Lekhnovich VS. 1983. New taxons [taxa] within the species Solanum andigenum Juz. et Buk. (in Russian with Latin diagnoses). Trudy po Prikladnoj Botanike Genetike i Selekcii 79: 45 - 49.", "Juzepczuk SW, Bukasov SM. 1929. A contribution to the question of the origin of the potato. Trudy Vsesoyuznogo S \" zeda po Genetike i Selektsii Semenovodstvu i Plemennomu Zhivotnovodstvu, 3: 593 - 611 (in Russian, English summary). Leningrad.", "Bukasov SM. 1930. The cultivated plants of Mexico, Guatemala and Colombia. Trudy po Prikladnoj Botanike Genetike i Selekcii, Supplement 47: 191 - 226, 513 - 525.", "Hawkes JG, Hjerting JP. 1989. The potatoes of Bolivia: their breeding value and evolutionary relationships. Oxford: Oxford University Press.", "Hawkes JG. 2004. Hunting the wild potato in the South American Andes. Memories of the British Empire potato collecting expedition to South America 1938 - 1939. Nijmegen: Botanical and Experimental Garden, University of Nijmegen.", "Bukasov SM. 1933. The potatoes of South America and their breeding possibilities. Trudy po Prikladnoj Botanike Genetike i Selekcii, Supplement 58: 1 - 192.", "Hawkes JG. 1944. Potato collecting expeditions in Mexico and South America. II. Systematic classification of the collections. Aberystwyth: Imperial Bureau of Plant Breeding and Genetics, 1 - 142."]}